(untitled) - Hicks, Carolyn M. (Edinburgh,New York, 1999)
This text provides a comprehensive introduction to research for allied health students and practitioners of all levels of experience. It offers an overview of major research approaches with emphasis on experimental methods and data analysis. With an aim to demystify research methods and statistical analysis, this book makes it easier for practitioners to conduct their own research and be able to critically evaluate published material. Practical coverage directly relates what is learned to the clinical situation. Efficient, to-the-point information provides a straightforward description of research design issues.
Keywords: Physical therapy,Research design,Statistics,Liệu pháp vật lý,Thống kê; Research,Methods,Nghiên cứu,Phương pháp